Duikers kleur- en materiaalgebruik. Het kleurpalet van de Derde Ambachtschool vergeleken met Cineac, Zonnestraal en Gooiland (Bulletin KNOB, 2000)
Even in the case of recent 'historic buildings', the original use of colour can often be hidden beneath later finishes. When the Derde Ambachtsschool (The Hague, 1930, by architect Jan Duiker in collaboration with Bernard Bijvoet) was restored, a special investigation looked into the use of colour and materials, with surprising results.It is often unjustly assumed that buildings of the Modern Movement were white, black and grey. This is probably the consequence of so many black and white photographs. But in recent years is has been increasingly recognised that the Modern Movement was familiar with colour. This chapter deals with the colours of the Derde Ambachtsschool and compares them with a number of Duiker's other buildings of the 1930s. It is evident that his architecture used colours: the question is, which?Research on the colours of the Derde Ambachtsschool was undertaken using the techniques of materials science. An aluminium colour was found on the render of the external walls, but this seemed to be an insulating coat under a grey finish. Laboratory analysis showed that the aluminium coat had been scraped clean and that the grey layer was a modern paint, as one of the pigments in it was only much used after the Second World War (titanium dioxide in the anatase-form).On the basis of this documentation, a fresh study was made of the tenders, accounts and documentation for the building. In the event the school did turn out to have had an original finish of aluminium colour! Elements of steel like garage doors and fences were also coloured aluminium. The steel window frames, doors and sills were dark blue. The plinth was covered in a rough, granitic black-grey layer of cement, while the chimney was a dark colour, and clear glass and glass blocks completed the look of the elevations.Inside, the same blue was there to be discovered on the window frames, doors and stills, as well as on the balustrade of the staircase (with chromium-plated handrails) and cupboards. The walls and ceilings were in a chalk-white stucco. The classrooms had light-grey panelling, while the corridors were finished in white 'Fortoliet', a type of polished cement.In the administrative offices, the rooms were panelled with a flat, polished finish, as were the doors, to make it clear that students were not allowed there. Yellow-ochre and brown tiles in the corridors also defined the children's routes. The school's colour-range consisted of calm colours: aluminium, dark blue and black outside; white, light grey, dark blue, chrome and aluminium inside, combined with the warmth of brown, ochre and polished wood in a light tone.Similar ranges of colour and materials may be found in other buildings of the 1930s by Duiker: at the Zonnestraal complex and the Gooiland Hotel in Hilversum, and the Cineac in Amsterdam. So the use of colour appears typical for Duiker at this time. The tendency of Duiker's architecture to allude to a machine-architecture and to lightness and transparency of form can be recognised in the use of colours here.The architectural references to the aesthetic of liners in the Derde Ambachtsschool are reinforced by the metallic nature of the aluminium paint, which also gives the feeling of lightness and transparency. Like the architecture, the finishing was also technically adventurous for its time, when aluminium paint was only used for things like steel fencing. In the blue of the window frames Duiker lets a subtle hint at the colour of the Dutch sky enter in.